Traditional agricultural practices in Suceava county, Romania - Mihai Alexandru Chiţea; Marioara Rusu; Violeta Florian; Lorena Chiţea; Elisabeta Roşu; Gabriel Simion (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
The present paper focuses on the agricultural practices of the dairy farms from Dornelor Basin, Suceava county, regarding grassland management, livestock feed, livestock disease management, aiming to evaluate the relationship between traditional and ecological practices, based on the expected increase in the near future of the ecological farming in the area. The scientific approach turns to a comparative analysis, based on a structured communication method - Delphi, involving 10 experts/local actors and to a large-scale farm survey applied to 52 dairy farms from the Dornelor Basin area. The results highlight a correlation between experts' opinion regarding the most important practices for defining an ecological farm and the traditional agricultural practices of the dairy farms from the study area, as these can be considered, to a high extend, to be ecological practices.
Keywords: Q01; Q57; 330; farm's characteristics; traditional agricultural practices; ecological practices